Using Eye-Tracking Technology to Assess the Effect of Daily Safety Training on Hazard Recognition Skills - Liu, Peng; Zhang, Chengyi; Arditi, David; Li, Huimin; Demirkesen, Sevilay (IEEE-Inst Electrical Electronics Engineers Inc, 2024)
Hazard recognition skills are a critical factor in construction safety. Eye-tracking technology is considered the direct and objective way to study hazard recognition issues. The article aims to evaluate the effect of daily safety training on people's hazard recognition skills using eye-tracking technology. The article focuses on three aspects: 1) effect of safety backgrounds (safety certifications, construction-related education, and construction-related work experience) on people's hazard recognition performance; 2) impact of daily safety training on hazard recognition skills and on the scan path of workers with varying backgrounds; and 3) comparison of the impact of daily safety training on the scan path of people with different hazard recognition levels. An eye-tracking experiment was conducted to obtain participants' eye movement data and achieve the article's objectives. The results of the article indicate that people who are educated in a related field of study demonstrate an advanced level of hazard recognition abilities, while safety certificates and construction-related work experience do not appear to have a significant impact. Following daily safety training, the participants exhibited more careful examination of construction scenarios. Additionally, individuals with higher hazard recognition levels displayed increased confidence in their hazard recognition judgments. This article makes a significant contribution to the existing body of knowledge by demonstrating the potential of eye-tracking technology to investigate the effect of safety training on visual scan paths. The results of this article emphasize the importance of considering various safety training methods for workers with varying hazard recognition levels to enhance their performance in identifying hazards.
Keywords: Daily safety training; eye-tracking technology; safety backgrounds; scan path